1990: A Search for Reconciliation - Atiba, Ihsan (Religion & gender, 2026)
This visual essay is an autobiographic account of Islam and masculinity in Trinidad, a society where colonially established hierarchies of race, religion, and class continue to shape lived experiences and social relations. I use a combination of visual art and auto-ethnography to examine inter-generational experiences and legacies of religion, politics and gender in order to deconstruct and examine my perceived identity.